Зависит ли значение выражения от значения x 4 (3x-2) -2(5x-1)-(2x-9)​

podynov8807 podynov8807    1   07.05.2021 16:46    0

Ответы
ask52 ask52  07.05.2021 16:50

-27

Пошаговое объяснение:

Если х=4

Дано: (3x-2) -2(5x-1)-(2x-9)​=3х-2-10х+2-2х+9=3х-10х-2х+9=-9х+9.

х=4, то -9×4+9=-27

ПОКАЗАТЬ ОТВЕТЫ
orliniyglassoyccc0 orliniyglassoyccc0  07.05.2021 16:50

Пошаговое объяснение:

4(3х-2)-2(5х-1)-(2х-9)=12х-8-10х+2-2х+9=12х-12х+11-8=3 при любом х так как х сокращается

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика